Studi Fenomenologi: Pengalaman Keluarga Merawat Penderita Pasca Stroke di Kota Jambi Tahun 2019 - kadarwati kadarwati; Rahmi Ulfa; Elvi Oktarina (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Stroke has a negative impact on families who provide care for post-stroke patients, the effect of which is due to functional deficits experienced by post-stroke sufferers which result in dependence on families for daily activities. The research objective was to explore in depth the experiences of families caring for post-stroke sufferers in Jambi city in 2019. This study used a qualitative method with a descriptive phenomenology approach. Participants in this study amounted to nine people who were selected using purposive sampling. Data is collected by semi-structured interview in duration of 60-90 minutes. Data analysis using the colaizzi method. The results found four themes, namely: dependence on daily activities on the family, family efforts to fulfill self-care activities, constraints faced by caregivers and family expectations. Conclusion: Families experience limited knowledge and skills, difficulties in meeting patients' ADLs, changes in physical conditions, changes in rest and sleep, changes in psychological conditions, changes in social activities, and economic changes. Therefore families need to get education from doctors, nurses and stroke team members starting from the time the patient is admitted to the hospital and re-evaluated when the patient is going home, about the knowledge and skills to treat post-stroke patients at home.